Efficient Routing In Wsn Using Enhanced Fuzzy Logic - Sarath kumar, A; Durga Kaveri, M; B.V Bhargavi, K; Naga Swetha, N; Priyanka, K (International Journal of Engineering and Technology, 2018)
In order to gather info additional precisely, wireless detector networks (WSNs) square measure divided into clusters. The cluster provides a good merit to make longer the period of WSNs. Topical clump comes close to usually use 2 methods: choosing cluster heads with additional enduring energy, and turning cluster heads sporadically, to distribute the energy consumption among nodes in every cluster and extend the network period. However, most of the previous algorithms haven't thought of the expected residual energy, that is, that the predicated left behind energy for being hand-picked as a cluster head and running around. During this paper, a fuzzy-logic-based clump approach [22] with associate degree conservatory to the energy postulation has been planned to lengthen the period of WSNs by equally distributing the work. The simulation results show that the planned come close to is additional more economical than alternative distributed algorithms. It's believed that the practice given during this paper can be any applied to extensive wireless detector networks.Â Â